Production and purification of high-titer OrfV for preclinical studies in vaccinology and cancer therapy - Jacob P. van Vloten (Elsevier, 2021)
Poxviruses have been used extensively as vaccine vectors for human and veterinary medicine and have recently entered the clinical realm as immunotherapies for cancer. We present a comprehensive method for producing high-quality lots of the poxvirus Parapoxvirus ovis (OrfV) for use in preclinical models of vaccinology and cancer therapy. OrfV is produced using a permissive sheep skin-derived cell line and is released from infected cells by repeated freeze-thaw combined with sonication. We present two methods for isolation and purification of bulk virus. Isolated virus is concentrated to high titer using polyethylene glycol to produce the final in vivo-grade product. We also describe methods for quantifying OrfV infectious virions and determining genomic copy number to evaluate virus stocks. The methods herein will provide researchers with the ability to produce high-quality, high-titer OrfV for use in preclinical studies, and support the translation of OrfV-derived technologies into the clinic.